2003
DOI: 10.1046/j.1365-2958.2003.03420.x
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria meningitidis App, a new adhesin with autocatalytic serine protease activity

Abstract: SummaryNeisseria meningitidis is a Gram-negative bacterium which colonizes the human upper respiratory tract. Occasionally, it translocates to the bloodstream causing sepsis and from there it can cross the blood-brain barrier and cause meningitis. Many of the molecules, which mediate the interaction of N. meningitidis to host cells, are still unknown. Recently, App (Adhesion and penetration protein) was described as a member of the autotransporter family and a homologue to the Hap (Haemophilus adhesion and pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
98
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 32 publications
3
98
0
Order By: Relevance
“…There is scarce evidence regarding their adhesin activity, specifically in directing attachment of bacteria to epithelial cells. For example, the protein App, produced by Neisseria meningitidis, is a determinant of adherence capacity to Chang cells (30). On the other hand, RpeA and Hap produced by rabbit enteropathogenic E. coli and Haemophilus influenzae, respectively, are able to direct adherence to epithelial cells when they are expressed in nonadherent strains of their respective species (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…There is scarce evidence regarding their adhesin activity, specifically in directing attachment of bacteria to epithelial cells. For example, the protein App, produced by Neisseria meningitidis, is a determinant of adherence capacity to Chang cells (30). On the other hand, RpeA and Hap produced by rabbit enteropathogenic E. coli and Haemophilus influenzae, respectively, are able to direct adherence to epithelial cells when they are expressed in nonadherent strains of their respective species (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…For IgA1, Hap, and, more recently, App, it has been demonstrated that the cleavage was the result of an autoprocessing event involving the integral serine protease active sites of the autotransporter, present in the passenger domain (206,401,445). AIDA-I is also thought to be autoprocessed, although no serine protease motif has been found (472).…”
Section: Autotransporter Secretion Pathway (Type Va)mentioning
confidence: 99%
“…The outer membrane-localized precursor is surface accessible, and antibodies raised against recombinant App exhibit bactericidal activity against the homologous strain (182). Recently, Serruto et al (445) have confirmed that App is an important virulence determinant, which mediates adhesion to epithelial cells (but not endothelial cells). Indeed, App is the first nonpilus protein to be shown to possess adhesive properties in the presence of the polysaccharide capsule.…”
Section: N Meningitidis App and Mspa Autotransporter Proteinsmentioning
confidence: 99%
“…Genome mining to investigate meningococcal autotransporters from whole-genome sequences identified several minor adhesion proteins: App (39), NhhA (36,40), MspA (52), and TspA (30). In addition, NadA has also been identified as an adhesion and invasion factor in human epithelial cells (5).…”
mentioning
confidence: 99%